Anemia as a mediator: bridging the frailty index and hip fractures in older Chinese populations - Li, Changqing; Zhao, Xiaojiang; Zhang, Lei; Ma, Chao; Zhang, Wenbo; Ding, Hong (Frontiers in Public Health, 2025)
BackgroundHip fracture is a significant global public health issue. The link and mechanisms between frailty index (FI) and hip fracture remain unclear. This research examined how anemia mediates the link between FI and hip fracture.MethodsThe study analyzed data from the 2015 China Health and Retirement Longitudinal Study (CHARLS), which included 6,326 participants aged 60 and above. The mediating role of anemia in the relationship between FI and hip fracture was examined using bootstrap analysis and linear regression models.ResultsAfter controlling for confounding variables, FI was positively associated with hip fracture (OR = 1.13, 95% CI: 1.09–1.16; p < 0.001). Anemia was also positively associated with hip fracture (OR = 1.88, 95% CI: 1.33–2.64; p < 0.001). Mediation analysis showed that anemia indirectly affected the relationship between FI and hip fracture, accounting for 18.95% of the total effect. Subgroup analysis showed that compared with non-frail and non-anemic participants, frail and anemic participants had a significantly increased risk of hip fracture (OR = 4.61, 95% CI: 2.80–7.61). However, no interaction between frailty and anemia was observed for hip fracture risk.ConclusionsThe findings suggest that FI and anemia were positively associated with hip fracture, and anemia played a mediating role in the association between FI and hip fracture. Intervention based on exercise, nutrition and medical management can combat anemia and reduce FI and may be an effective way to prevent or delay hip fractures.